Examining the role of mother-child interactions and DNA methylation of the oxytocin receptor gene in understanding child controlling attachment behaviors. Issue 1 (2nd January 2021) - Lecompte, V.; Robins, S.; King, L.; Solomonova, E.; Khan, N.; Moss, E.; Nagy, C.; Feeley, N.; Gold, I.; Hayton, B.; Turecki, G.; Zelkowitz, P.
ABSTRACT: This study examined mother-child interactions and DNA methylation of the oxytocin receptor (OXTR) gene in the child, in relation with controlling-attachment behaviors at early preschool age. Maternal interactive behaviors were coded using the Emotional Availability Scales, and child attachment behaviors were assessed with the Separation-Reunion procedure and coded with the Preschool Attachment Rating Scales. DNA methylation data were captured from exon 3 of the OXTR. Results indicated that lower maternal sensitivity was associated with more controlling-caregiving behaviors, and that less maternal structuring was associated with more controlling-punitive behaviors. Hypomethylation of the OXTR gene was associated with greater maternal structuring behaviors, and with more child controlling-caregiving behaviors. The moderating role of the OXTR gene was examined in the association between interactive behaviors and child controlling behaviors, but no interaction effect was found. These results suggest that maternal interactive behaviors and OXTR methylation are independently associated with child controlling attachment.